HIPNOLAKTASI MENINGKATKAN KOMITMEN IBU DALAM PEMBERIAN ASI EKSKLUSIF DI SURABAYA - Masruroh, Nur; Laili, Uliyatul (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Breast Milk (ASI) contains high nutrients that are very beneficial for infant health. World Health Organization, WHO recommends infants get exclusive breastfeeding for 6 months (Infodatin, 2016) Support from the nearest person will be instrumental in the success of breastfeeding. Breastfeeding is also inseparable from the mother's commitment to breastfeeding. Efforts that can be done in the process of breastfeeding mother is hypnolaktasi techniques. This study aims to determine the effect of hypnolaktasi on mother's commitment in giving exclusive breastfeeding to her baby. This research uses a qualitative approach and the type of research is descriptive. Samples were taken by purposive sampling. The data were collected by giving an open questionnaire and interviewing the mother about hypnolactation and mother's commitment to exclusive breastfeeding to her baby. The results showed that 75% of respondents were 25-30 years old, 58% had 1 child and 83% had good knowledge about exclusive breastfeeding. Based on the interview results obtained that the benefits after doing the hypnolactation perceived the respondents are comfortable in breastfeeding and confident breastfeeding can go out smoothly and 5 respondents who do not provide infant formula to the baby until now. The conclusions of this study are knowledge, and management of hypnolactation can increase the mother's commitment in exclusive breastfeeding. Keywords: hypnolactation, mother's commitment, Exclusive breastfeeding